1980
DOI: 10.1017/s0001566000007923
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Inheritance of Some Anthropometric Characters in Twins

Abstract: Biometrical genetical techniques have been applied to the analysis of certain anthropometric characters measured in 134 pairs of adult twins. After allowing for assortative mating it appears that there is a family environment (E2 ) component for variation in height larger than previously reported. "Fatness" traits -weight, ponderal index, and skinfold thickness -all show higher heritabilities in males and substantial Ez components in females, and reasons for this are discussed. The same is true for cephalic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The results of this analysis (Table 2) showed that DZ regressions were no greater than their MZ counterparts. Because this test has proved powerful in detecting genetical non-additivity for other traits in much smaller samples [4,18], we conclude that directional non-additivity is not an important source of variation in alcohol consumption. A sensible hierarchy of models is to first fit E!…”
Section: Genetical Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…The results of this analysis (Table 2) showed that DZ regressions were no greater than their MZ counterparts. Because this test has proved powerful in detecting genetical non-additivity for other traits in much smaller samples [4,18], we conclude that directional non-additivity is not an important source of variation in alcohol consumption. A sensible hierarchy of models is to first fit E!…”
Section: Genetical Analysismentioning
confidence: 83%
“…Alternative models of trait variation are fitted to between-and within-pairs mean squares by iterative weighted least squares [4,8,9]. A chi-square test of goodness of fit, based on expected mean squares calculated from the least-squares parameter estimates, provides a test of the adequacy of each model.…”
Section: Genetical Analysismentioning
confidence: 99%
“…This was so irrespective of sex and absorption versus elimination. Age per se is not an inherited trait and weight, adiposity, and lung function are incompletely inherited (Clark et al, 1980;Gibson et al, 1983), so the contribution of these four variables to the heritable portion of total BAC variance must also have been small.…”
Section: Discussionmentioning
confidence: 99%
“…A full model incorporating different sized El, VA and E2 effects for males and females [Clark et al, 1980;Eaves et al, 19781 was therefore tried. If the genes affecting a trait in males are quite different from those affecting the trait in females, then VAmf (the covariance between the genetic effects in males and females) will be zero.…”
Section: Genetic Analysismentioning
confidence: 99%